2001
DOI: 10.2174/1568009013334151
|View full text |Cite
|
Sign up to set email alerts
|

D-RNAi (Messenger RNA-antisense DNA Interference) as a Novel Defense System Against Cancer and Viral Infections.

Abstract: D-RNAi (Messenger RNA-antisense DNA interference), a novel posttranscriptional phenomenon of silencing gene expression by transfection of mRNA-aDNA hybrids, was originally observed in the effects of bcl-2 on phorbol ester-induced apoptosis in human prostate cancer LNCaP cells. This phenomenon was also demonstrated in chicken embryos and a human CD4 + T cell line, H9. The in vivo transduction of β-catenin DRNAi was shown to knock out more than 99% endogenous β-catenin gene expression, while the in cell transfec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“… 27 29 siRNAs inhibit specific gene expression by inducing the sequence-specific degradation of homologous mRNA, which knocks down the gene product at the posttranscriptional level. 30 32 In the current study, wild-type (WT) and PXR-knockdown mice were used to assess the effects of PXR on the Tan IIA treatment of DSS-induced IBD. 14 Results indicated that Tan IIA could ameliorate DSS-induced IBD in a dose-dependent manner, and the effects were exerted by the activation of PXR and inhibition of the expression of inflammatory mediator genes in vivo.…”
Section: Introductionmentioning
confidence: 99%
“… 27 29 siRNAs inhibit specific gene expression by inducing the sequence-specific degradation of homologous mRNA, which knocks down the gene product at the posttranscriptional level. 30 32 In the current study, wild-type (WT) and PXR-knockdown mice were used to assess the effects of PXR on the Tan IIA treatment of DSS-induced IBD. 14 Results indicated that Tan IIA could ameliorate DSS-induced IBD in a dose-dependent manner, and the effects were exerted by the activation of PXR and inhibition of the expression of inflammatory mediator genes in vivo.…”
Section: Introductionmentioning
confidence: 99%